2010
DOI: 10.1016/j.stem.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty1 Regulates Reversible Quiescence of a Self-Renewing Adult Muscle Stem Cell Pool during Regeneration

Abstract: SummarySatellite cells are a heterogeneous population of skeletal muscle specific stem cells capable of self-renewal and differentiation after transplantation. Whether quiescent satellite cells can self-renew and contribute to muscle fiber repair in their endogenous environment in normal regenerating muscle has remained unknown. The transcription factor Pax7 is expressed in satellite cells and is critical for establishing the adult satellite cell pool. Using a temporally-inducible genetic lineage tracing appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
308
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 283 publications
(318 citation statements)
references
References 50 publications
10
308
0
Order By: Relevance
“…49,50 However, satellite cells are capable of self-renewal and differentiation during repair. 20,21 This confirms that adult Pax7 + satellite cells have stem cell properties in their endogenous environment.…”
Section: Muscle Satellite Cellssupporting
confidence: 54%
See 3 more Smart Citations
“…49,50 However, satellite cells are capable of self-renewal and differentiation during repair. 20,21 This confirms that adult Pax7 + satellite cells have stem cell properties in their endogenous environment.…”
Section: Muscle Satellite Cellssupporting
confidence: 54%
“…However overexpression studies have demonstrated that Pax7 is sufficient to promote a return to quiescence through repression of MyoD and myogenin 35,37 suggesting downregulation of MyoD is a critical component of reversible quiescence. During the proliferative phase of regeneration in vivo, the majority of the satellite cells that repopulated the renewed Pax7 + stem cell pool progressed through a MyoD + state, 21 therefore expressing MyoD during developmental history does not exclude a satellite cell from returning to quiescence in vivo.…”
Section: Muscle Satellite Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…6A). During regeneration, the satellite cell pool expands in response to the injury, before differentiating to repair the damaged area and returning to a baseline satellite cell number, maintaining the stem cell population [39,50]. While the p38a fl muscle responded to the muscle injury as expected by displaying a 10-fold satellite cell number increase and returning to baseline levels by 25 DPI, the p38a KO muscle displayed a heightened satellite cell expansion ( Fig.…”
Section: Acute Injury In P38a Ko Mice Results In a Prolonged Satellitmentioning
confidence: 81%